PPARγ induces growth inhibition and apoptosis through upregulation of insulin-like growth factor-binding protein-3 in gastric cancer cells - Kim,S.Y. (2015)
Peroxisome proliferator activator receptor-gamma (PPARγ) is a ligand-activated transcriptional factor involved in the carcinogenesis of various cancers. Insulin-like growth factor-binding protein-3 (IGFBP-3) is a tumor suppressor gene that has anti-apoptotic activity. The purpose of this study was to investigate the anticancer mechanism of PPARγ with respect to IGFBP-3. PPARγ was overexpressed in SNU-668 gastric cancer cells using an adenovirus gene transfer system. The cells in which PPARγ was overexpressed exhibited growth inhibition, induction of apoptosis, and a significant increase in IGFBP-3 expression. We investigated the underlying molecular mechanisms of PPARγ in SNU-668 cells using an IGFBP-3 promoter/luciferase reporter system. Luciferase activity was increased up to 15-fold in PPARγ transfected cells, suggesting that PPARγ may directly interact with IGFBP-3 promoter to induce its expression. Deletion analysis of the IGFBP-3 promoter showed that luciferase activity was markedly reduced in cells without putative p53-binding sites (-Δ1755, -Δ1795). This suggests that the critical PPARγ-response region is located within the p53-binding region of the IGFBP-3 promoter. We further demonstrated an increase in PPARγ-induced luciferase activity even in cells treated with siRNA to silence p53 expression. Taken together, these data suggest that PPARγ exhibits its anticancer effect by increasing IGFBP-3 expression, and that IGFBP-3 is a significant tumor suppressor.